2019
DOI: 10.3390/educsci9040296
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Undergraduate Research into Social Science Curriculum: Benefits and Challenges of Two Models

Abstract: Evidence shows that undergraduate research is beneficial to students during their college years and beyond. This study evaluates two models for integrating undergraduate research into the college curriculum: (1) integrating a community-based research project into a social science course and (2) designing a senior seminar course as an undergraduate research experience. Findings show that students benefit from a hands-on research experience that deepens their understanding of both survey methods and social issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…In this scenario, research becomes an educational principle fundamental for the training of students and provides an environment for dialogue and critical discussion. In this way, it awakes students to autonomous and participatory learning and teaches them how to learn (Crowe & Boe, 2019;Demo, 2015;Galiazzi & Moraes, 2002). Scientific Initiation (SI) programs have great relevance because they strengthen scientific initiation, introduce students to scientific research, and promote their application in academic and professional master's degrees and doctorate programs (Brazil, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, research becomes an educational principle fundamental for the training of students and provides an environment for dialogue and critical discussion. In this way, it awakes students to autonomous and participatory learning and teaches them how to learn (Crowe & Boe, 2019;Demo, 2015;Galiazzi & Moraes, 2002). Scientific Initiation (SI) programs have great relevance because they strengthen scientific initiation, introduce students to scientific research, and promote their application in academic and professional master's degrees and doctorate programs (Brazil, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Undergraduate students build a strong academic foundation through research including critical thinking skills and oral and written communication skills. 20 A survey of medical students showed that a large proportion of students who were positive about a career in research felt that it would enable them to make advances in the medical field. Additionally, others felt that it was necessary for career progression, satisfaction, and an overall integral component of becoming a medical practitioner.…”
Section: The Benefits Of Researchmentioning
confidence: 99%
“…Nowadays the European Higher Education Area (EHEA) encourages the usage of active learning methodologies through practice and the development of curricula focused on the acquisition of key competencies based on the project method (Ayensa et al, 2019). These changes in the educational area show the relevance of conducting new scientific research, which allows determining the degree of effectiveness of the project method as the main instrument and its impact on the motivation of students to research and collaborate with employers (Crowe & Boe, 2019, Fernandes et al, 2018Kobarg et al, 2018).…”
Section: Global Tendencies In the Development Of Higher Education Systemmentioning
confidence: 99%